Games Advertising Vs Tv Advertising Which One Is More Effective In Building Brands? - Albertus Edward Goutama (Jurnal Ekonomi, 2018)
There are a many pros and cons regarding which are more effective between TV Advertising and Games Advertising in being a medium of promotion media. As we know TV Advertising and Games Advertising is widely used big companies in promoting a product as well as embed Brand Image and Brand in Mind Set society in general. This article shows a number of pentung points that make TV Advertising is superior to a number of advantages it has , Compared Games Advertising in promoting a product.